2022
DOI: 10.3390/polym14235139
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole Nanomaterials: Structure, Preparation and Application

Abstract: In the past decade, nanostructured polypyrrole (PPy) has been widely studied because of its many specific properties, which have obvious advantages over bulk-structured PPy. This review outlines the main structures, preparation methods, physicochemical properties, potential applications, and future prospects of PPy nanomaterials. The preparation approaches include the soft micellar template method, hard physical template method and templateless method. Due to their excellent electrical conductivity, biocompati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 258 publications
(337 reference statements)
3
22
0
Order By: Relevance
“…Various highly elastic polymeric materials have been selected as flexible substrates/dielectric layers as well as sensing materials and electrodes to assemble flexible pressure sensors due to their excellent deformability and simple manufacturing processes, including polydimethylsiloxane (PDMS) [ 17 ], poly(vinylidene fluoride) (PVDF) [ 17 ], polyvinyl alcohol (PVA) [ 18 ], polyethylene (PEN) [ 19 ], polyethylene terephthalate (PET) [ 20 ], polymethyl methacrylate (PMMA) [ 21 ], polyimide (PI) [ 12 ], polyurethane (PU) [ 22 ], polycarbonate (PC) [ 23 ], Ecoflex [ 24 ], epoxy [ 25 ], etc. Other conductive polymers such as polypyrrole (PPy) [ 26 ], polyaniline (PANI) [ 27 ], and hybrid poly(3,4-ethylenedioxythiophene) (PEDOT) [ 28 , 29 ] have shown higher electrical conductivity and excellent mechanical flexibility as wearable pressure sensors [ 30 ].…”
Section: Polymersmentioning
confidence: 99%
“…Various highly elastic polymeric materials have been selected as flexible substrates/dielectric layers as well as sensing materials and electrodes to assemble flexible pressure sensors due to their excellent deformability and simple manufacturing processes, including polydimethylsiloxane (PDMS) [ 17 ], poly(vinylidene fluoride) (PVDF) [ 17 ], polyvinyl alcohol (PVA) [ 18 ], polyethylene (PEN) [ 19 ], polyethylene terephthalate (PET) [ 20 ], polymethyl methacrylate (PMMA) [ 21 ], polyimide (PI) [ 12 ], polyurethane (PU) [ 22 ], polycarbonate (PC) [ 23 ], Ecoflex [ 24 ], epoxy [ 25 ], etc. Other conductive polymers such as polypyrrole (PPy) [ 26 ], polyaniline (PANI) [ 27 ], and hybrid poly(3,4-ethylenedioxythiophene) (PEDOT) [ 28 , 29 ] have shown higher electrical conductivity and excellent mechanical flexibility as wearable pressure sensors [ 30 ].…”
Section: Polymersmentioning
confidence: 99%
“…10−12 Polypyrrole (Ppy) is an intrinsically conducting polymer with good aqueous stability and allows surface functionalization. 12,13 Reports confirm that Ppy NPs increase cardiac conduction velocity, synchronize irregular cardiac rhythm, and enhance Ca 2+ signaling across cardiac cells, although in vitro. 7,14 However, some studies indicated that high concen- trations of Ppy NPs could affect its biocompatibility and cause undesirable effects.…”
Section: Introductionmentioning
confidence: 96%
“…Polypyrrole (Ppy) is an intrinsically conducting polymer with good aqueous stability and allows surface functionalization. , Reports confirm that Ppy NPs increase cardiac conduction velocity, synchronize irregular cardiac rhythm, and enhance Ca 2+ signaling across cardiac cells, although in vitro. , However, some studies indicated that high concentrations of Ppy NPs could affect its biocompatibility and cause undesirable effects. − A recent study of p -toluene sulfonic acid-doped Ppy NPs reported that at high concentrations (500 ÎŒg/mL) caused embryonic toxicity, premature hatching, and a reduced heart rate in zebrafish larvae .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among the known conducting polymers, PPy is extensively used in commercial applications owing to its high conductivity, high energy density, good durability, and low toxicity [ 6 , 7 ]. PPy is extensively used in many applications, including electrocatalysts, sensors, rechargeable batteries, and biomedicines [ 8 , 9 , 10 ]. The structure and conductivity of polymers play important roles in determining their efficiency in various applications.…”
Section: Introductionmentioning
confidence: 99%